Geração de segundo harmônico em cristais bidimensionais de nitreto de boro - Egleidson Frederik do Amaral Gomes (2017)
In general the physical properties of materials depend intrinsically on symmetries. A property clearly dependent on symmetry is the ability of non-centrosymmetric materials to generate light with twice the incident frequency, an effect named second harmonic generation (SHG). The effect is absent for centrosymmetric materials. In this work we present results for hexagonal boron nitride (h-BN) nano-crystals studied by second harmonic generation microscopy. The h-BN is a heterostructure of nitrogen and boron, whose odd layers have no inversion symmetry and therefore have the necessary condition for the generation of the second harmonic. We present results for samples that underwent thermal treatment that lead to wrinkle formation. We show that the wrinkles are formed from origami-like joints, and preferentially follow the crystal armchair direction. Our results also show that the second harmonic generation microscopy allows access to information of the crystalline topography that is not easily observed by other types of microscopy. We also show results of the SHG intensity dependence on the number of layers for samples with few layers and a monolayer of h-BN. We present a comparative study between samples with and without heat treatment. The results show that the intensity of the SHG signal decreases with the increase in the number of layers, but the layer number dependence is different for each type of sample.